Self-regulated multimedia learning in sport science concepts and a field study - Wiemeyer, J.; Schmitz, B. (Proceedings of the 10th International Symposium on Computer Science in Sports (ISCSS), 2016)
To fully exploit the potentials of e-learning, learners have to take more responsibility for their own learning. According to models of selfregulated learning (SRL), learners have to actively engage in planning, execution and reflection of their learning activities. The purpose of this paper is to present a study on the effects of an SRL training on multimedia learning in sport science. Twenty students attending a course in biomechanics of sport were randomly assigned to a self-regulation training (SRT) or a no-training (NO-SRT) group. The SRT group underwent an SRL training. Before and after the learning period of 2 weeks, the students` knowledge and self-confidence was tested. Although the SRT group spent more time with the program than the NO-SRT group, there was no learning benefit. Test performance of both groups significantly increased from pretest to posttest.